Racialized narratives in Dutch history textbooks: a critical race examination - Sijpenhof, Maria Luce (Historia y Memoria de la Educación, 2019)
The current article is a qualitative analysis of racialized narratives in Dutch textbooks (1968-2017), illustrated by eight exemplary depictions of Black people selected from a sample of 200 Dutch secondary school history textbooks. Because images are indicators of racialization, the author focuses on visual narratives. The article concludes that racialization is displayed through two types of narrative structures: a) racialization through otherness using one-sided stereotypical identities and racial hierarchy and b) racialization through sameness maintained through colorblind frames, racialized narratives and minimization of race-talk. The article furthermore reflects on the use of critical race theory (CRT) as a framework and the use of critical race methodology (CRM) in combination with discursive methods for textbook and visual analysis. By inserting counter narratives, this article illustrates that the field of history of education, especially in Europe, could make better use of critical (race) frameworks and research tools that do not divorce historical events from contemporary and persisting injustices.